Sinonasal adenoid cystic carcinoma: a population‐based analysis of 694 cases. Issue 3 (11th November 2016) - Unsal, Aykut A.; Chung, Sei Y.; Zhou, Albert H.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Background: Currently, limited literature exists about sinonasal adenoid cystic carcinoma (SNACC). In this study, we analyze the demographics, survival, and treatment efficacy of this rare entity. Methods: Our study was a retrospective population‐based analysis of SNACC in the Surveillance, Epidemiology, and End Results (SEER) database assessing the 40‐year time‐frame of 1973 to 2013. Results: Six hundred ninety‐four SNACC patients were identified; 53.2% were female and 46.8% were male. Caucasians were most commonly affected (77.1%). SNACC most often arose from the maxillary sinuses, followed by the nasal cavity. The majority of SNACC cases presented as stage IV disease. Nodal and distant metastases were present in 3.6% and 7.1% of all cases, respectively. Overall 5‐, 10‐, and 20‐year disease‐specific survival (DSS) rates were 66.5%, 41.1%, and 17.6%, respectively. The presence of distant metastasis dropped the 5‐year DSS rate from 64.5% to 20.0%. Cases treated with combined surgery and adjuvant radiotherapy had a slightly improved 5‐year DSS rate compared with surgery alone (73.5% vs 72.5%). Surgery alone resulted in higher 10‐ and 20‐year DSS rates (54.2% and 36.8%, respectively) when compared with combined therapy (44.2% and 15.5%), radiotherapy alone (10.8% and 0%), and no surgery or radiotherapy (9.3% and 0%). Conclusion: This study represents the largest cohort of SNACC patients to date. Factors that confer a survival benefit in SNACC include M0 disease, and presentation primarily in the nasal cavity. Overall low rates of nodal metastasis may not warrant the use of elective neck dissections, unless there is clinical suspicion. Modalities of therapy that include surgery greatly improve survival. Adjuvant radiotherapy appears to slightly improve 5‐year disease‐free survival but does not impact long‐term survival.